The determinants of transfer pricing: Evidence from Tunisian listed firms - Kasraoui, Abdelkader; Naoui, Kamel (WIM Solusi Prima, 2024)
The aim of this paper is to detect the determinants of transfer pricing in the Tunisian economic context. This study uses secondary data from financial statments of listed firms on the Tunis Stock Exchange (BVMT), as well as the notes published in the official bulletins and annual reports provided by the Tunisian Financial Market Council (CMF).The study period covered 10 years, from 2010 to 2019 with 310 observations. We use random effect model to verify financial and economic hypotheses in the Tunisian context. Robustness tests are also used to investigate the transfer pricing determinants’. We find that firm size, sector of activity, reinvestment of profits and tax loss’ imputation have a significant positive impact on the practice of transfer pricing. The originality of this study lies in the importance of the transfer pricing at the level of local companies with the presence of several tax rates in the same tax system, a range of tax incentives granted by the government and the imputation of perpetual loss over several years.These findings may serve the Tunisian government in its fight against transfer pricing.